A computational avenue towards understanding and design of zwitterionic anti-biofouling materials. Issue 14 (13th October 2019) - Shao, Qing
ABSTRACT: This review introduces a computational avenue towards understanding and design of zwitterionic anti-biofouling materials. Biofouling means nonspecific adsorption of proteins, cells, and bacteria on materials and devices. It can sabotage materials functions and bring detrimental effects on the biological systems. Various anti-biofouling materials have been developed and zwitterionic materials emerge as promising candidates recently. The design and understanding of zwitterionic anti-biofouling materials rely on the answers of three fundamental questions: (a) what molecular properties govern the anti-biofouling performance of materials, (b) what is the structure–property-anti-biofouling relationship for materials, and (c) how to identify anti-biofouling materials based on the revealed mechanisms? This paper discussed the efforts of answering the three questions using molecular simulations. We first discuss the simulations that revealed the importance of hydration in the anti-biofouling performance of materials and why this mechanism leads to the discovery of zwitterionic anti-biofouling materials, then the simulations that investigated structure-properties-performance relationships of zwitterionic anti-biofouling materials, and the development of computational approaches that can identify zwitterionic anti-biofouling molecules. Finally, we discuss the opportunities in understanding and design of anti-biofouling biomaterials using computer simulations.